Korean university students’ significant learning experiences and associated generic skills: A qualitative essay review - Lee, Ahram; Lee, Soo Jeung (Frontiers in Education, 2022)
The purpose of the present study was to explore the learning experiences that university students identify as being significant and derive generic skills integrated in those learning experiences. The study implemented document analysis to analyzed essay data collected from 33 students in a four-year university in Seoul, Korea. A total of 102 excerpts were coded, forming 14 clusters, which were categorized into 5 themes that describe the significant learning experience, namely interacting with others, learning by oneself and about oneself, realizing applicability to real life, venturing into advanced learning, and experiencing respectful learning atmosphere. Also, 18 generic skills were identified which were categorized into 4 clusters, comprehensive thinking skills, information utilization skills, interpersonal skills, and personal attributes. The results of the present study provide the ground work for understanding the relations between significant learning experiences and generic skills.